2017
DOI: 10.1680/jgere.16.00018
|View full text |Cite
|
Sign up to set email alerts
|

Research-oriented ground investigation projects at Changi, Singapore

Abstract: The Changi East Reclamation projects in Singapore were implemented in five phases starting from 1991 and completed in 2005. Due to the excessive magnitude of settlement likely to occur over a long period of duration caused by the consolidation process, an extensively large area was required to be improved using ground improvement techniques to accelerate the consolidation process. The planning and implementation of site investigation works for land reclamation projects is discussed in this paper. An accurate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, such a test should allow defining the unconfined compressive strength for different orientations of soil samples in the ground so that the effect of inherent anisotropy in the form of cracks, layers or discontinuities can be investigated. Modern soil sampling and rock coring techniques (e.g., block samples, large diameter oil-operated samplers, rotary sidewall coring) and subsequent coring in the laboratory must be used in order to achieve very good quality samples for subsequent laboratory testing (Agarwal et al 2014;ASTM D2113-14, 2014Bo et al 2017;BS EN ISO 22475-1, 2006;Chung et al 2014;Gylland et al 2014;Long et al 2010).…”
Section: Materials Parametersmentioning
confidence: 99%
“…However, such a test should allow defining the unconfined compressive strength for different orientations of soil samples in the ground so that the effect of inherent anisotropy in the form of cracks, layers or discontinuities can be investigated. Modern soil sampling and rock coring techniques (e.g., block samples, large diameter oil-operated samplers, rotary sidewall coring) and subsequent coring in the laboratory must be used in order to achieve very good quality samples for subsequent laboratory testing (Agarwal et al 2014;ASTM D2113-14, 2014Bo et al 2017;BS EN ISO 22475-1, 2006;Chung et al 2014;Gylland et al 2014;Long et al 2010).…”
Section: Materials Parametersmentioning
confidence: 99%
“…The study conducted by Sridharan, and Nagaraj (2000) summarised the available equations for compression index of different soils and shown in In addition, Bo et al (2017) suggested correlations of compressibility index for Singapore marine clays as follows. 2019) performed FEM of the oedometer test using PLAXIS 2D program to assess the stress-strain response of medium-dense sand.…”
Section: An Oedometer Test To Investigate the Consolidation Of Soilsmentioning
confidence: 99%